Overweight, Obesity, And Related Diseases Among Workers With Different Workload - Pavlina Gidikova; Gergana Sandeva; Kamelia Haracherova; Rositsa Sandeva (Journal of Biomedical & Clinical Research)
A person's weight depends on major factors like genetics, diet, and physical activity. Physical activity in adults is defined mainly by workload – light, moderate or heavy. The aim was to explore associations between weight and chronic non-infectious diseases in workers with different physical activity. The subjects included in the study were 224 male and 249 female employees, divided by workload based on their job description. Body mass index (BMI) and disease incidence were calculated, and statistical analysis was performed. The highest percentage of overweight and obese subjects was found in men with light workload. The mean BMI for men (27.434.85) was significantly higher than that for women (25.875.06). Analysis of obesity-associated diseases showed that in workers with higher BMI there was a higher incidence of endocrine disorders, musculoskeletal and related neurological diseases. Diseases of the circulatory system were highly prevalent in both overweight/obese and underweight employees. In conclusion, physical activity at work contributes to changes in BMI in the working population. Obesity-associated circulatory, endocrine and musculoskeletal diseases were highly prevalent in the groups with higher BMI. The prevalence in employees without diseases was in inverse relation to BMI.